2021
DOI: 10.3390/genes12121904
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomics Analysis of Lens from Patients with Posterior Subcapsular Congenital Cataract

Abstract: To gain insight into the aetiology of posterior subcapsular congenital cataract from the perspective of transcriptional changes, we conducted an mRNA sequencing analysis of the lenses in posterior subcapsular congenital cataract patients and in normal children. There were 1533 differentially expressed genes from 19,072 genes in the lens epithelial cells of the posterior subcapsular congenital cataract patients compared to in the normal controls at a cut-off criteria of |log2 fold change| of >1 and a p-value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…p val < 0.05, including 250 upregulated and 165 downregulated DEGs. 40 R visualized the volcano plot ( Figure 1A ) and heatmap ( Figure 1B ) of the DEGs.
Figure 1 Differentially expressed genes identified in the two datasets GSE1919 and GSE77298.
…”
Section: Resultsmentioning
confidence: 99%
“…p val < 0.05, including 250 upregulated and 165 downregulated DEGs. 40 R visualized the volcano plot ( Figure 1A ) and heatmap ( Figure 1B ) of the DEGs.
Figure 1 Differentially expressed genes identified in the two datasets GSE1919 and GSE77298.
…”
Section: Resultsmentioning
confidence: 99%
“…Recently, COL11A1 has been recruited as novel biomarker and a key player in cancer ( 24 ). COL11A1 is expressed in the mouse lens including the fiber cells ( 25 ) and in the zebrafish model, COL11A1, its knockdown affected lens and optic cup diameter during early development ( 26 ) indicative of a functional role in the lens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the purpose of this study is to explore the potential mechanism of its occurrence and development. Previously, we performed transcriptome sequencing of capsules from patients with PSC and normal controls and found that HTRA1 was the most significant candidate pathogenic gene in lens epithelial cells [11]. HTRA1 has been previously detected in the lenses of mice [12].…”
Section: Introductionmentioning
confidence: 99%